2022
DOI: 10.1002/ags3.12605
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding may be a promising prognostic indicator in intrahepatic cholangiocarcinoma: A multicenter retrospective study

Abstract: Purpose This retrospective study evaluated our hypothesis that high tumor budding (≥10 buds) may help determine the appropriate T category for more accurate staging of intrahepatic cholangiocarcinoma (ICC). Methods We analyzed the clinical and histopathologic data of 235 consecutive patients with histologically confirmed ICC following hepatectomy at five university hospitals in the Kansai region of Japan between January 2009 and December 2020. ICC staging was based on the Liver Cancer Study Group of Japan (LCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…TB is also an important prognostic indicator in CRC, and the prognostic significance of TB has also been reported in other types of carcinomas, regardless of the histological type of cancer (both adenocarcinoma and squamous cell carcinoma) (18)(19)(20)(21)(22). For example, Noda et al recently analyzed the significance of DR, TB, tumor-infiltrating lymphocytes, and depth of invasion of oral squamous cell carcinoma to determine its ability to predict extranodal extension, which is an important indicator of poor prognosis for this type of carcinoma (21).…”
Section: Discussionmentioning
confidence: 89%
“…TB is also an important prognostic indicator in CRC, and the prognostic significance of TB has also been reported in other types of carcinomas, regardless of the histological type of cancer (both adenocarcinoma and squamous cell carcinoma) (18)(19)(20)(21)(22). For example, Noda et al recently analyzed the significance of DR, TB, tumor-infiltrating lymphocytes, and depth of invasion of oral squamous cell carcinoma to determine its ability to predict extranodal extension, which is an important indicator of poor prognosis for this type of carcinoma (21).…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, a full‐text review was performed, during which studies with inadequate data or cohort presentation, as well as those lacking full‐text availability, the inadequate study design was excluded. Ultimately, 57 studies met our inclusion criteria and were included in our systematic review and meta‐analysis 4,5,16–70 . Manual‐checking references to ensure comprehensives did not yield any additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies classified TB into low and intermediate/high groups based on the cut-off value of 5 [ 11 , 12 , 14 , 15 , 18 ]. Conversely, Kosaka et al reported a difference in the survival outcomes between low/intermediate and high TB groups, using a cut-off value of 10 in their multicenter study [ 13 ]. As in Kosaka’s study, we divided patients with TB into low/intermediate and high groups.…”
Section: Discussionmentioning
confidence: 99%
“…By introducing this concept, studies on the prognostic significance of TB in various cancer types, such as pancreatic, gallbladder, esophageal, and gastric cancers, have been conducted [7][8][9][10]. Although relevant studies have recently been performed to evaluate the importance of TB in CC, the number remains limited, and only 10 papers have been published to date (as of March 2023) [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%